Political development under the rule of Mohammad Reza Pahlavi in Iran (1953-1979) - Karimi, Maryam (2015)
This thesis seeks to explore the process of political development in Iran during the reign of Mohammad Reza Pahlavi from 1953 to 1979. This period represents the age of Iran’s modernization. The Pahlavi regime’s attitude and practices regarding political development had raised much criticism in domestic and international circles and subsequently brought about the 1979 Islamic Republic Revolution in Iran. While Pahlavi's regime had its own plan of development for Iran, it was the very same plan which helped to prevent the simultaneous genesis of a distinct process of political development in Iran. This study assesses events which were direct outcomes of conflicts between Mohammad Reza Pahlavi's development plan and factors of political development in Iran from 1953 to 1979. This was to be the salient problem at the root of the issue of Iran’s political development. This research is conducted on political development process during the pre and post-1953 event in Iran. Perspectives of universality, monarchy, and nation-building have been important in this study. Just as any thesis is constructed upon theories, this research has presented the theories of, nationalism, modernization and institutionalization but the nationalism is applied theory of this research. The approach and method of this study is qualitative content analysis. This study also examines the political development changes and progress plans under Mohammad Reza Pahlavi's rule and his attitudes on political development. If not for the deficiencies in his measures, there would not have been so many weaknesses in the process of political development that consequently led to the Revolution of 1979. The findings of this study determine the factors of political development, analyzing and challenges to Iran’s political development during the rule of Mohammad Reza Pahlavi, since 1953 to 1979. This study examines the impact of political development actors and elites upon internal and external affairs that undermined challenges of Iranian regime attitude upon the political development process in Iran during 1953-1979.